SOME LEGAL ISSUES ON THE CURRENT MANAGEMENT OF TAX INDIVIDUAL BUSINESS HOUSEHOLDS IN VIETNAM - Nguyen Thi Hai Yen (Journal of Applied Science and Technology, 2019)
The legal framework on tax administration for individual business households has been gradually improved, contributing to the State’s purpose of mobilizing the budget revenue from business households; At the same time, it helps tax administration agencies to easily manage taxes for individual business households. From the problems and difficulties in tax administration, the paper proposes a number of recommendations to further improve regulations on tax administration for business households.